Foreign Investors and Global Integration of Emerging Indian Equity Market - Poshakwale, Sunil S.; Thapa, Chandra (SAGE Publications, 2010)
This article examines the influence of foreign investors in explaining short-run dynamics and long-run relationship of the emerging Indian equity market with global equity markets. Using daily return series and equity portfolio investments made by foreign institutional investors, we conclude that the rapid growth in the flow of foreign equity portfolio investments is leading to greater integration of the Indian equity market with global markets. With the increased global integration, the Indian market will become more susceptible to global shocks as has been witnessed by significant losses suffered by investors in the Indian market following the sub-prime crisis.